Four‐Extremity Neurostimulation Using Two Cervical Octapolar Leads and High Frequency of 10 kHz. Issue 2 (4th June 2017) - Harandi, Shervin; Kapural, Leonardo
Abstract: Objectives and Methods: A few published reports describe successful clinical use of low‐frequency spinal cord stimulation (SCS) in the cervical spine resulting in bilateral upper and lower extremity pain relief. A major side‐effect when using this modality of SCS is the uneven intensity of paresthesias, which are frequently excessive in upper extremities while attempting to achieve optimal paresthesia coverage in all 4 extremities. Results and Conclusions: Here we describe a successful case of high‐frequency SCS at 10 kHz where profound control of neuropathic pain of all 4 extremities was achieved without the complication of paresthesias. Discussed are future implications of such therapy.